Nuevos fundamentos sobre la lex Adriana: la inscripción de Lella Drebblia - Sanz Palomera, Gustavo (Gerión. Revista de Historia Antigua, 2008)
A new epigraphic document sheds new light on the Imperial policy concerning the known Imperial Estates in Africa Proconsularis. The lex Hadriana was one of the most important laws promoted by the Roman emperors, attempting to increase the agricultural production of properties under their direct authority.